PEMANFAATAN LIMBAH KULIT KOPI ARABIKA (COFFEA ARABIKA L.) MENJADI BIOBRIKET - lisani, Lisani (PPPM POLTESA, 2023)
The amount of plantation waste materials, one of which is coffee husk waste by 35% which has the potential to be used as biobriquettes as an alternative fuel is coffee skins. The cellulose content of coffee skin is quite high. This study aims to determine the quality of biobriquettes from tapioca flour adhesive in the process of making Arabica Coffee Skin Waste Biobriquettes and to determine the most appropriate tapioca starch adhesive for Arabica coffee skin waste biobriquettes. The tapioca starch adhesive composition used is 5%, 10%, 15%, 20% and 25%. Analysis of this coffee husk waste Biobriquette with reference to the Indonesian National Standard (SNI). The analysis was carried out on the calorific value analysis test, the moisture content test analysis, the ash content analysis test, and the combustion rate. The values that meet the Indonesian National Standard are the Analysis of Moisture Content of 5.69% and the Analysis of Ash Content with a value of 7.86%, while the Analysis of Calorific Value of 3224 cal/g, and the Burning Rate of 0.351 g/minute do not meet the Indonesian National Standard.